Busca pelo homem social nas organizações: indícios, constatações, possibilidades - Bittencourt, Francisco Rage (2003)
This study approaches the question of organizations in search for competitiveness when globalization, knowledge and technological advances in the First World is a challenge in developing countries. The case study research focus on Bahia Sul ¿ a large organization which belongs to the important sector of paper and cellulose, especially in terms of exports. This study analyses an organization in that underpriviledged situation of a third world country in which the majority of organizational strategies are heavily thrown on people who are simultaneously reduced to instruments for economic results and who are highly demanded in terms of productivity and creativity. Due to that reality, references chosen present two key contrasting concepts. Mass man, going back to Taylor¿s blue collars as well as to Marcel¿s knowledgeable but empty words man, whose abilities do not feet his needs, in contrast with rogerian expectations of person as a mutable and continuously enriched human being and with habermasian position looking for political and decision making participation in work an social situations. Results show a strong presence of mass man, despite his technological knowledge, and scarce indications of the social man and which appears in mere aspirations out of labor situations. Conclusions emphasize a need for coherence between organizational practices in search for competitiveness and expectations on persons¿ performance because they stimulate exchanges in terms of working places for obedience and some material comfort which is aggravated by the fact that any possibility of personal fulfillment is interpreted as only possible in out of work situations. Competitiveness in such a context is not to be expected.